Classification modeling based on surface porosity for the grading of natural cork stoppers for quality wines - Oliveira, Vanda; Knapic, Sofia; Pereira, Helena (Food and Bioproducts Processing)
Abstract The natural cork stoppers are commercially graded into quality classes according with the homogeneity of the external surface. The underlying criteria for this classification are subjective without quantified criteria and standards defined by cork industry or consumers. Image analysis was applied to premium, good and standard quality classes to characterize the surface of the cork stoppers and stepwise discriminant analysis (SDA) was used to build predictive classification models. The final goal is to analyze the contribution of each porosity feature and propose an algorithm for cork stoppers quality class classification. This study provides the knowledge based on a large sampling to an accurate grading of natural cork stoppers.
Keywords: Classification algorithm; Discriminant analysis; image analysis; natural cork stoppers; Porosity; quality classes

NATURAL VARIABILITY OF SURFACE POROSITY OF WINE CORK STOPPERS - Oliveira, Vanda; Knapic, Sofia; Pereira, Helena (Journal international des sciences de la vigne et du vin, 2012)
Aim : The aim of this study was to characterize the variability and to quantify the surface porosity of wine cork stoppers of different quality classes. Methods and results: The porosity of 300 cork stoppers was characterized by image analysis on the lateral surface and tops. Porosity coefficient was 2.4%, 4.0% and 5.5% for premium, good and standard stoppers, respectively. The lateral surface of stoppers was heterogeneous with respect to porosity features: the tangential regions presented higher porosity while the radial regions had larger pores. Conclusion : The quality classes of cork stoppers can be differentiated by the mean values of the main porosity features of their surface. There is a natural heterogeneity of the porosity features over the external surface of cork stoppers that can be traced back to the biological basis of cork formation and the production process. Significance and impact of the study: Natural cork stoppers are the premium product of the cork industry, with worldwide recognition of quality and performance as wine sealant. Due to the large sampling and detailed observation, the results presented in this study may be used for reinforcing quality requirements, e.g., with definition of standards to improve the classification system. A better understanding of cork intrinsic variability and of the anisotropy of porosity features shown by cork stoppers is important for performance development.
Keywords: image analysis; lateral surface; natural cork stoppers; Porosity; quality classes

NATURAL VARIABILITY OF SURFACE POROSITY OF WINE CORK STOPPERS - Oliveira, Vanda; Knapic, Sofia; Pereira, Helena (Journal international des sciences de la vigne et du vin, 2012)
Aim : The aim of this study was to characterize the variability and to quantify the surface porosity of wine cork stoppers of different quality classes. Methods and results: The porosity of 300 cork stoppers was characterized by image analysis on the lateral surface and tops. Porosity coefficient was 2.4%, 4.0% and 5.5% for premium, good and standard stoppers, respectively. The lateral surface of stoppers was heterogeneous with respect to porosity features: the tangential regions presented higher porosity while the radial regions had larger pores. Conclusion : The quality classes of cork stoppers can be differentiated by the mean values of the main porosity features of their surface. There is a natural heterogeneity of the porosity features over the external surface of cork stoppers that can be traced back to the biological basis of cork formation and the production process. Significance and impact of the study: Natural cork stoppers are the premium product of the cork industry, with worldwide recognition of quality and performance as wine sealant. Due to the large sampling and detailed observation, the results presented in this study may be used for reinforcing quality requirements, e.g., with definition of standards to improve the classification system. A better understanding of cork intrinsic variability and of the anisotropy of porosity features shown by cork stoppers is important for performance development.
Keywords: image analysis; lateral surface; natural cork stoppers; Porosity; quality classes

Decision rules for computer-vision quality classification of wine natural cork stoppers - Costa, Augusta; Pereira, Helena (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 2006)
Image-analysis techniques were applied to the surface of wine cork stoppers (tops and bodies) of the standard seven commercial quality classes to characterize their porosity. Canonical discriminant analysis (CDA) and stepwise discriminant analysis (SDA) were used to differentiate quality class and to identify the best features to select these classes. The accuracy of classification using CDA functions was on average greater than 50% for the seven commercial classes and was greater than 67% for a simplified three-grade classification. Based on the independent variables of the first CDA function determined by the stepwise method, a set of features was selected for use in decision rules for cork stopper classification: porosity coefficient and maximum pore dimensions (length and area) for bodies and porosity coefficient and number of pores for tops. Threshold limits for each feature were established for each quality class and a classification algorithm was applied. Results showed an overall match in class yield of 86% and better class homogeneity and separation. These are proposed as a foundation for future standardization of cork stopper classification based on image analysis and computerized vision systems selection of quantified features to ensure uniformity and transparency in trade while maintaining the overall economical feasibility in industrial processing.
Keywords: canonical discriminant; quality classes; wine cork stoppers

Decision rules for computer-vision quality classification of wine natural cork stoppers - Costa, Augusta; Pereira, Helena (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 2006)
Image-analysis techniques were applied to the surface of wine cork stoppers (tops and bodies) of the standard seven commercial quality classes to characterize their porosity. Canonical discriminant analysis (CDA) and stepwise discriminant analysis (SDA) were used to differentiate quality class and to identify the best features to select these classes. The accuracy of classification using CDA functions was on average greater than 50% for the seven commercial classes and was greater than 67% for a simplified three-grade classification. Based on the independent variables of the first CDA function determined by the stepwise method, a set of features was selected for use in decision rules for cork stopper classification: porosity coefficient and maximum pore dimensions (length and area) for bodies and porosity coefficient and number of pores for tops. Threshold limits for each feature were established for each quality class and a classification algorithm was applied. Results showed an overall match in class yield of 86% and better class homogeneity and separation. These are proposed as a foundation for future standardization of cork stopper classification based on image analysis and computerized vision systems selection of quantified features to ensure uniformity and transparency in trade while maintaining the overall economical feasibility in industrial processing.
The following values have no corresponding Zotero field: pub-location: PO BOX 1855, DAVIS, CA 95617-1855 USA publisher: AMER SOC ENOLOGY VITICULTURE
Keywords: canonical discriminant; quality classes; wine cork stoppers

Quality characterization of wine cork stoppers using computer vision - Costa, a; Pereira, H (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2005)
Image analysis techniques were applied on the surface of wine cork stoppers (tops and lateral cylindrical surface) of seven commercial quality classes to characterize their porosity. An increasing trend from the best to the worst quality classes was found for features related to area of pores (i.e. maximum length and width or pore maximum area) and concentration variables (i.e. porosity coefficient or number of pores per 100 cm(2)). Shape variables were rather constant and mean values showed no differences between quality classes. Variation of the pores characteristics within each quality class was large especially in the mid-quality range. Therefore there were no statistically significant differences to allow the isolation of the all quality classes and overlapping was particularly important in the medium-quality classes. The reduction of grading into only three quality classes allowed to isolate statistically different subsets based on porosity coefficient and number of pores per 100 cm(2). These variables can be selected for further development into quality grades specification of wine cork stoppers.
Keywords: computer imaging; quality classes; wine cork stoppers

Quality characterization of wine cork stoppers using computer vision - Costa, A.; Pereira, H. (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2005)
Image analysis techniques were applied on the surface of wine cork stoppers (tops and lateral cylindrical surface) of seven commercial quality classes to characterize their porosity. An increasing trend from the best to the worst quality classes was found for features related to area of pores (i.e. maximum length and width or pore maximum area) and concentration variables (i.e. porosity coefficient or number of pores per 100 cm(2)). Shape variables were rather constant and mean values showed no differences between quality classes. Variation of the pores characteristics within each quality class was large especially in the mid-quality range. Therefore there were no statistically significant differences to allow the isolation of the all quality classes and overlapping was particularly important in the medium-quality classes. The reduction of grading into only three quality classes allowed to isolate statistically different subsets based on porosity coefficient and number of pores per 100 cm(2). These variables can be selected for further development into quality grades specification of wine cork stoppers.
The following values have no corresponding Zotero field: pub-location: 42 RUE MARSAN, 33300 BORDEAUX, FRANCE publisher: VIGNE ET VIN PUBLICATIONS INT
Keywords: computer imaging; quality classes; wine cork stoppers